Exploratory Factor Analysis of the Real Behaviors Associated with Virtues, Ethics and Desirable Values of Undergraduate Students - พิภพเอกสิทธิ์, ไพโรจน์; อนันทวิจักษณ์, สรวงอัยย์ (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
The purposes of this research were to study exploratory factor analysis of the real behaviors associated with virtues, ethics and desirable values of undergraduate students, and to propose guideline to develop the virtues, ethics and desirable values of undergraduate students. The instruments used in the research were online questionnaires (Google Forms) and the quality was cheked by 3 experts. The data were collected from sample of undergraduate students studying in Bangkok Metropolitan Region, Eastern and North-eastern and Northern are 400 samples. The samples were selected by convenience sampling method. An exploratory factor analysis was carried out using the methodology for the exploratory factor with principal component analysis as well as the orthogonal rotation with varimax rotation method. The findings revealed that the studied variables could be analysed amount 7 factors which were realize knowledge of resource and environment, self-reliance, commitment to work, public spirit, gratitude, refrain from drugs and honesty. The commulative variance could describe as 68.728. The results of general suggestions were found that the respondents proposed the following guidelines for the development of virtues, ethics and desirable values of the undergraduate students i.e. 1) The presidenet of universities, lecturers and students should be encouraged to develop and cultivate the virtues, ethics and desirable values of undergraduate students continuously. And 2) teaching and learning related to virtues, ethics and desirable values should be included training and workshop activities to increase motivation students to real practice.